The Role of Cadmium-Resistant Bacterial Application and Compost in Promoting Water Spinach Growth and Reducing Cadmium Uptake - Novrianty Rizqi Azis; Yulia Nuraini; Reni Ustiatik; Cahyo Prayogo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The continuous use of chemical fertilizers and pesticides in soil can result in the presence of cadmium (Cd) residues that may interfere with plant growth and pose a risk of uptake by plants. The issue of soil contamination by Cd can be addressed through soil bioremediation, which involves the use of Cd-resistant bacteria and compost. The objective of this study was to analyze the impact of Cd-resistant bacteria and compost application on the growth and Cd uptake of water spinach. The research design was a completely randomized design with seven treatments: (1) control, (2) 5 mL Cd-resistant bacteria consortium, (3) 10 mL Cd-resistant bacteria consortium, (4) 10 tons/ha compost, (5) 20 tons/ha compost, (6) 5 mL Cd-resistant bacteria consortium +10 tons/ha compost, and (7) 10 mL Cd-resistant bacteria consortium +20 tons/ha compost. The results demonstrated that the application of Cd-resistant bacteria and compost did not notably impact the growth of water spinach. However, it did significantly influence the reduction of Cd uptake in water spinach. The application of the Cd-resistant bacterial consortium and compost was effective in reducing the Cd uptake of the water spinach plants in all treatments. The combination of 10 mL of bacterial isolate and 20 tons/ha of compost demonstrated the greatest reduction in Cd uptake by water spinach, reaching 73%. Keywords: Bioremediation, Cadmium-resistan bacteria, Compost, Environmental monitoring, Soil contamination.